STRATEGI KOMUNIKASI DAKWAH PENYULUH AGAMA NON PNS DALAM MEMBINA MASYARAKAT DESA BATU NYADI KECAMATAN KETUNGAU HILIR KABUPATEN SINTANG - Darmawan Saputra (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
This study aims to find out the communication strategy of non-civil servant Religious Extension Workers in fostering rural communities which are formulated into three questions as follows: the role of Non-Civil Servant Religious Extension Workers in realizing rural communities. Diffusion of communication da'wah Non-civil servant Religious Extension in fostering rural communities and innovation of communication da'wah Non-civil servant Religious Extension in fostering rural communities in the district Ketungau Hilir Sintang district. The research method uses descriptive methods by making Non-Civil Servant Religious Extension of Sintang district that fosters rural communities as the main source in this research. This type of research is qualitative. The results showed that non-civil servant religious extension workers acted as agents of change by conducting persuasive-informative communication in resuscitating and fostering rural communities in ketungau hilir subdistrict of Sintang district. Diffusion of da'wah communication carried out by non-civil servant Religious Extension in fostering rural communities in the district ketungau Hilir Sintang district through activities in the form of ta'lim assembly and coaching da'wah cadres carried out at several points in the village of Beloh Mulyo, Indung Sepring, Mengaret and Batu Nyadi Village. Da'wah communication innovation carried out by non-civil servant religious extension workers in the form of implementation of da'wah cadreization program in the village through training activities and ta’lim assembly.